2007
DOI: 10.1007/s10549-007-9839-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel BRCA1 large genomic rearrangement in a Spanish breast/ovarian cancer family

Abstract: The new mutation here reported broadens the mutational spectrum of large rearrangements. Furthermore, the five large rearrangements found in patients non-carriers of BRCA1/BRCA2 mutations reinforce the need of studying BRCA1 large genomic rearrangements in genetic counselling programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The deletion of exons 4-6 of BRCA1 (in the literature also referred to as BRCA1 del exons 5-7) detected for a single White non-Afrikaner BC patient is rare, as it has been detected only six times previously, mostly in European countries, namely Germany [25], Croatia [36], Italy [37], Slovenia [38], Spain [39] and Denmark [40]. For some of these deletions, the breakpoints were determined [25,39,40]. Preisler-Adams et al [25] determined that a homologous region of 15 bp between AluSx in intron 3 and AluSc in intron 7 at the crossover site, is responsible for this LGR in German families.…”
Section: Discussionmentioning
confidence: 99%
“…The deletion of exons 4-6 of BRCA1 (in the literature also referred to as BRCA1 del exons 5-7) detected for a single White non-Afrikaner BC patient is rare, as it has been detected only six times previously, mostly in European countries, namely Germany [25], Croatia [36], Italy [37], Slovenia [38], Spain [39] and Denmark [40]. For some of these deletions, the breakpoints were determined [25,39,40]. Preisler-Adams et al [25] determined that a homologous region of 15 bp between AluSx in intron 3 and AluSc in intron 7 at the crossover site, is responsible for this LGR in German families.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that this sequence contains a recombinogenic hotspot as assumed for other sequences in Alu elements, as also postulated before. 18,19 Rüdiger et al, 19 suggested that four different rearrangements in the low density lipoprotein receptor gene presented a 26-bp common sequence that functions as a recombinational hotspot. This core sequence contains a pentanucleotide motif (CCAGC), which is also part of chi, an 8-bp sequence known to stimulate recBC-mediated recombination in Escherichia coli.…”
Section: According To Sluiter and Van Rensburg 4 81 And 17 Differentmentioning
confidence: 99%
“…Of the published studies of the frequency of BRCA1 / 2 LGRs in the Iberian Peninsula or regions thereof [6][17], none has specifically examined the population of Galicia (NW Spain), a region with a distinct genetic identity attributable to its historical relative isolation, its cultural identity, and the occurrence of a marked population bottleneck around 1000 years ago [18]. This population features a number of founder mutations [18][20], including a BRCA1 mutation, c.211A>G (referred to NM_007294.3; BIC 330A>G), which is present in more than 50% of Galician HBOC families with BRCA1/2 mutations [21].…”
Section: Introductionmentioning
confidence: 99%